Dan Taylor and the Old General Baptists. (3rd April 2018) - Copson, Stephen
ABSTRACT: Dan Taylor helped to found the New Connexion of General Baptists. He strongly disagreed with the Old General Baptists on some key theological issues. And yet the New Connexion maintained links with the General Assembly for many years, and the two bodies discussed reunion several times. This paper seeks to explore this relationship which continued until Taylor withdrew from the General Assembly.